Enhancing Students' Science Process Skills through the Implementation of POGIL-based General Chemistry Experiment Manual: A Quantitative Study - Faizah Qurrata Aini; Zonalia Fitriza; Iswendi Iswendi; Ifan Rivaldo; Mawardi Mawardi; Annisa Khairani Putri (Universitas Pendidikan Mandalika, 2023)
This study focuses on the development of a POGIL-based experiment manual for general chemistry courses to enhance students' science process skills. The research and development (R&D) method, utilizing the Plomp model, was employed to create a valid and practical manual. Data were collected through a validity and practicality questionnaire, which was then analyzed using the Kappa Cohen's method. The manual's content was found to be highly valid, with an average score of 0.82, while its graphics had an average score of 0.84, also falling within the high category. Practicality was assessed through small group student testing, revealing high practicality scores in terms of user convenience, attractiveness, and benefits, with an average score of 0.77. Overall, the results indicate that the POGIL-based general chemistry experiment manual developed in this study is both valid and practical.